2023
DOI: 10.1073/pnas.2213093120
|View full text |Cite
|
Sign up to set email alerts
|

Learning critically drives parkinsonian motor deficits through imbalanced striatal pathway recruitment

Abstract: Dopamine (DA) loss in Parkinson’s disease (PD) causes debilitating motor deficits. However, dopamine is also widely linked to reward prediction and learning, and the contribution of dopamine-dependent learning to movements that are impaired in PD—which often do not lead to explicit rewards—is unclear. Here, we used two distinct motor tasks to dissociate dopamine’s acute motoric effects vs. its long-lasting, learning-mediated effects. In dopamine-depleted mice, motor task performance gradually worsened with tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…Levodopa (L‐Dopa) and subthalamic deep brain stimulation (STN‐DBS) shift the balance towards the direct pathway and thereby counteract the chronic weakening present in the PD OFF state. (b) In line with a reinforcement‐centred framework, a recent rodent study (Cheung et al, 2023) has shown that Parkinsonian motor decline and medication‐induced rescue are task and experience‐dependent. Mice were trained on two tasks (step/pole task) before unilaterally lesioning dopamine neurons with 6‐hydroxydopamine (6‐OHDA), which induced a contralateral motor deficit (fewer steps with the contralateral paw).…”
Section: Understanding Parkinson's Disease As a Disorder Of Neural Re...mentioning
confidence: 96%
See 4 more Smart Citations
“…Levodopa (L‐Dopa) and subthalamic deep brain stimulation (STN‐DBS) shift the balance towards the direct pathway and thereby counteract the chronic weakening present in the PD OFF state. (b) In line with a reinforcement‐centred framework, a recent rodent study (Cheung et al, 2023) has shown that Parkinsonian motor decline and medication‐induced rescue are task and experience‐dependent. Mice were trained on two tasks (step/pole task) before unilaterally lesioning dopamine neurons with 6‐hydroxydopamine (6‐OHDA), which induced a contralateral motor deficit (fewer steps with the contralateral paw).…”
Section: Understanding Parkinson's Disease As a Disorder Of Neural Re...mentioning
confidence: 96%
“…By suppressing indirect pathway activity, STN-DBS could reinstate the reinforcement homeostasis that is lost in PD and thereby support the intrinsic dopamine-driven strengthening that remains in PD (see Figures 4a and 3a). (Cheung et al, 2023) has shown that Parkinsonian motor decline and medication-induced rescue are task and experience-dependent. Mice were trained on two tasks (step/pole task) before unilaterally lesioning dopamine neurons with 6-hydroxydopamine (6-OHDA), which induced a contralateral motor deficit (fewer steps with the contralateral paw).…”
Section: Neural Reinforcement As a Target For Adaptive Deep Brain Sti...mentioning
confidence: 99%
See 3 more Smart Citations